Testing and Modelling of Building Envelope Retrofit System for Rapid Seismic Strengthening of Important RC Buildings - Can Balkaya (Modelling and Simulation in Engineering)
This article presents a new, rapid technique for retrofitting reinforced concrete buildings. With the “Structural Jacketing Building Envelope Retrofit System,” the entire outer shell of the building is retrofitted with steel struts that are connected to the reinforced concrete frame via dowels. The new system behaves like a composite system. As most of the seismic loads are absorbed by the new integrated external composite system, the structural elements inside the building are mainly loaded by gravity. In this way, the seismic performance and the lateral wind and torsional capacity of the retrofitted structures are increased by retrofitting the building envelope. The main advantage of this technique is the ability to retrofit existing buildings without compromising their serviceability and to quickly increase the seismic and wind capacity of buildings in regions with high seismicity and wind in the run-up to disasters. Thus, this system is a solution for retrofitting important building structures such as hospitals, schools, energy and telecommunication buildings, and factories that cannot be retrofitted within the building. In addition to retrofitting to achieve energy efficiency in existing buildings, cladding and insulation can be easily and cost-effectively applied to the retrofitted building envelope. Three-dimensional models of RC buildings with and without structural building envelopes were tested under static cyclic pushover loading to simulate 3D behavior, lateral load capacity, crack patterns, and collapse mechanisms under seismic loading. The results of the tests, finite element modelling, and simulation were compared to verify the proposed system. The tests and the analysis of the models show that the structures retrofitted in the building envelope increase their seismic resistance by four times. Analytical studies for building envelope retrofit systems were also conducted and compared using different braced models. The application of this system in the retrofit of a 10-story RC building in Istanbul is presented as a case study, including energy efficiency and architectural envelope.